Fertility preservation opportunities for cancer patients in Malaysia - Abdul Karim, Abdul Kadir; Ahmad, M. F.; Abdul Hamid, Habibah (Malaysian Medical Association, 2021)
Fertility preservation is significant for oncology patients to maintain their ability to start a family when they are ready. Onco-fertility, as a discipline, exists at the intersection of oncology and reproductive medicine that safeguards and expands the fertility options for cancer survivors, by facilitating early intervention and suitable treatment with favourable outcomes. Successful fertility preservation requires a comprehensive networking among the gynaecologists, oncologists, pathologists, imaging and other specialists, involved in diagnosing and treating cancer in the reproductive age group. There are several ways in which fertility can be preserved, like role of gonadotrophin releasing hormone analogues, in vitro maturation, and cryopreservation.